Deskripsi Makrofauna pada Tanah Andisol di Kabupaten Karo dengan Berbagai Ketebalan Abu Vulkanik Gunung Sinabung - Armando Septian Simbolon; Mariani sembiring; Tengku Sabrina (Jurnal Pertanian Tropik, 2018)
Changed soil conditions will result in the changed population and diversity in the soil. The eruption of Sinabung Mount caused the surface of the soil covered with volcanic ash with various thicknesses. This research was to study a description of macrofaunal communities at different thicknesses of Sinabung volcanic ash on andisol soil in Karo Regency. The experiment was conducted in May 2017. The experiment plot was located at four locations, location I was not covered by ash (0 cm), location II was covered with thin ash (≤2 cm), location III was covered with medium ash (2-8 cm), location IV was covered with thick ash (≥8 cm) using the transect sampling method. Samples was collected by using the Pitfall Trap, Monolith quadrant, and the Hand Sorting method. Macrofaunal communities found 3 phyla, 6 classes, 11 orders, 17 families, and 18 species at location I. Macrofaunal communities found 3 phyla, 7 classes, 11 orders, 16 families, and 17 species at location II. Macrofaunal communities found 2 phyla, 3 classes, 7 orders, 9 families, and 9 species at location III. Macrofaunal communities found 1 phylum, 2 classes, 5 orders, 7 families, and 7 species at location IV.